KUALITAS PAPAN PARTIKEL AMPAS SAGU BERDASARKAN KADAR PEREKAT ASAM SITRAT - Endriani, Beti; Setyawati, Dina; Nurhaida, . (Universitas Tanjungpura, 2019)
This research was to aimed the quality of particle board made from sago waste on citric acid. Particle board made from sago waste from Ambawang Subdistrict, the Regency of Kubu Raya. The research was conducted at the Wood Workshop Laboratory, Wood Processing Laboratory, Faculty of Forestry and PT. Duta Pertiwi Nusantara. Particle size with 8 mesh – 10 mesh and Adhesive citric acid levels were 10%, 20%, 30%, 40%. Mixing material is done manually. Particle board is made with size 30 cm x 30 cm x 1 cm with target density of 0,6 gr/cm2. specificpressure of 25 kg/cm2 and temperature of 1800 C for 15 minutes. The quality of particle board comply with a request JIS A 5908-2003 is increasing adhesive citric acid 20%.Keyword : citric acid, particle board, sago waste